Strategies to Improve Learning Achievement Through School-Based Management - Noor Sulistiyono; Hery Yanto; Tri Joko Raharjo; Sandy Arif (Universitas Negeri Semarang, 2023)
This study aims to describe in depth the Strategy to Improve Learning Achievement through School-Based Management at SMK Pelayaran Sinar Bahari Palembang. This study used a descriptive qualitative approach. Data collection is carried out by interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation and conclusions. Research informants are principals, vice principals and teachers. The results showed that ;(1) The implementation of management at SMK Pelayaran Sinar Bahari Palembang including all activities carried out openly and always coordinated with the school committee and even involved in both academic and non-academic activities. (2) A prominent supporting factor in the leadership of the principal at SMK Pelayaran Sinar Bahari Palembang, is teacher support. (3) Supervision carried out by the principal at SMK Pelayaran Sinar Bahari Palembang, including evaluations carried out after each activity.